Lumbar bone marrow microcirculation measurements from dynamic contrast-enhanced magnetic resonance imaging is a predictor of event-free survival in progressive multiple myeloma - Hillengaß, Jens; Wasser, Klaus; Delorme, Stefan; Kießling, Fabian; Zechmann, Christian; Benner, Axel; Kauczor, Hans-Ulrich; Ho, Anthony Dick; Goldschmidt, Hartmut; Möhler, Thomas (Clinical cancer research, 2007)
Purpose: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) with high temporal resolution enables the detection of microcirculation variables amplitude A and exchange rate constant kep. In this study, the prognostic value of the DCE-MRI variables for overall survival and event-free survival in patients with progressive multiple myeloma was investigated. - Experimental Design: Between 1999 and 2001, 65 patients with progressive or relapse of multiple myeloma requiring therapy were investigated with DCE-MRI of the lumbar spine before start of therapy. The contrast uptake was quantified using a two-compartment model with the output variables amplitude A and exchange rate constant kep reflecting bone marrow microcirculation. The estimated median follow-up was 56 months. Event-free survival and overall survival were investigated for DCE-MRI variables and for established prognosis variables (β2-microglobulin, lactate dehydrogenase, albumin, and age). - Results: Using a multivariate Cox regression model, β2-microglobulin and amplitude A of DCE-MRI were identified as statistically significant prognostic variable of event-free survival with Ps of 0.01 and 0.02, respectively. A statistical correlation of DCE-MRI variables with overall survival could not be found. The multivariate analysis of β2-microglobulin, age, lactate dehydrogenase, and albumin revealed β2-microglobulin as statistically significant prognostic factor for overall survival in this group of patients (P < 0.001). - Conclusions: This analysis identifies contrast-enhanced DCE-MRI variable amplitude A reflecting increased bone marrow microcirculation and angiogenesis as a novel and possibly useful prognostic factor in patients with multiple myeloma. Prospective studies are currently done to further investigate this functional variable for prognosis and stratification of myeloma patients.